Soil–structure interaction effects on seismic demand and fragility of CLT wall systems coupled with dissipating connectors - Konstantinos Skandalos; Anastasios Sextos; Solomon Tesfamariam (Soil Dynamics and Earthquake Engineering, 2026)

The 2020 Samos Island (Aegean Sea) earthquake: effects on cultural heritage structures - Christos Giarlelis; Constantinos Repapis; Anastasios Sextos; Elizabeth Vintzileou (Bulletin of Earthquake Engineering, 2026)

An Efficient Computational Seismic Testbed of a Nuclear Power Plant Diesel Generator Building - Angeliki Gerontati; Nikolaos D. Karaferis; Stelios Vernardos; Nikolaos Lesgidis; Anastasios G. Sextos; Nevena Šipčić; Paolo Bazzurro; Dimitrios Vamvatsikos (Bulletin of Earthquake Engineering, 2026)
The state-of-the-art in seismic hazard and risk assessment has evolved to encompass, among others, ground motion selection methods, clustered seismicity, and new fragility assessment approaches. In contrast, nuclear power plant safety assessment follows a more conservative path, adhering to established methods with limited scope for experimentation. Bridging the divide to test and potentially introduce novel concepts requires compatibility with current practice, while avoiding unnecessary modeling complexity. To address this, a low-order computational testbed is proposed within the EURATOM METIS project, to create a fast, open-source assessment platform. It focuses on the diesel generator building of the Zaporizhzhia VVER-1000 nuclear power plant and incorporates simplified models of the building, one non-structural component, and a bare-bones fault tree to propagate uncertainties efficiently for a scenario of loss of core cooling (LoCC). The impact of soil–structure interaction (SSI) is modeled using either equivalent-linear lumped-parameter assemblies with frequency-dependent properties or more advanced frequency- and intensity-dependent configurations. This streamlined setup enables researchers to explore advanced assessment methodologies and provides a practical benchmark for nuclear facilities. As part of the testbed evaluation, the effectiveness of two different ground motion intensity measures is assessed in conjunction with hazard-consistent versus randomly selected earthquake records for the site of interest. In all cases, incorporating SSI and hazard-consistent ground motions offers higher fidelity and more consistent risk estimates with lower conservatism. Coupling these with a more efficient intensity measure, such as average spectral acceleration, offers further improvements, to some extent ameliorating any lack of hazard consistency in record selection.

Ageing-dependent, multi-hazard fragility of monopile-supported offshore wind turbines - Ziliang Zhang; Raffaele De Risi; Anastasios G. Sextos (Soil Dynamics and Earthquake Engineering, 2026)

Shaking table tests of unreinforced and retrofitted rectangular three-leaf masonry walls under triaxial seismic excitation - Francesco Di Michele; Enrico Spacone; Giuseppe Brando; Guido Camata; Anastasios Sextos; Adam Crewe; George Mylonakis; Matt Dietz; Luiza Dihoru; Humberto Varum (Engineering Structures, 2025)

Evaluation of the Durrës station seismic record (ΜW=6.4, 26/11/2019) by means of structural damage assessment - Sotiria Stefanidou; Dimitrios Sotiriadis; Nikolaos Klimis; Basil Margaris; Nikolaos Theodoulidis; Anastasios Sextos (Bulletin of Earthquake Engineering, 2025)

Seismic response of bridges employing knowledge-enhanced neural networks for the lumped plasticity modelling of RC piers - Zhenliang Liu; Anxin Guo; Cunbao Zhao; Anastasios Sextos (Bulletin of Earthquake Engineering, 2024)
To facilitate seismic analysis of bridges, especially on a regional scale, this study established a parametric finite element model of bridges incorporating simplified component elements. It employs a knowledge-enhanced neural network (KENN) to calibrate the parameters of the lumped plasticity model of pier columns. Along with a database of historical experimental results, the influence of the key characteristics of reinforced concrete columns on model parameters are investigated and formulated as physical laws to supervise KENN training. The developed KENN model was then developed, yielding root mean square errors within the range of [0.027, 0.209]. These errors are slightly larger than those of the purely data-driven neural network, yet the KENN model aligns more consistently with the physical principles. Further, to demonstrate its accuracy and efficiency, the proposed methodology was applied for the rapid seismic response analysis of typical bridges.

Do soft soil layers reduce the seismic kinematic distress of onshore high-pressure gas pipelines? - Nikolaos Makrakis; Prodromos N. Psarropoulos; Anastasios Sextos; Yiannis Tsompanakis (Bulletin of Earthquake Engineering, 2024)
Onshore high - pressure gas pipelines constitute critical infrastructure that usually cross seismic - prone regions and are vulnerable to Permanent Ground Deformations (PGDs) due to active seismic faults. In design, it may not be feasible to avoid fault rupture areas due to various technical, economical and topographic reasons. Moreover, the presence of soil layers affects the PGDs resulting from a tectonic fault, which in turn may alter the seismic demand on the pipeline. The current study investigates numerically the impact of soft soil layers on the seismic kinematic distress of onshore gas pipelines. For this purpose, a decoupled numerical modeling approach is adopted, consisting of two separate finite - element models for the simulation of soil response and pipeline distress, respectively. Soil non - linearities are taken into account utilizing the Mohr - Coulomb constitutive model with isotropic strain softening. An extensive parametric analysis is performed considering different faulting mechanisms and fault dip angles, as well as soil geometry and mechanical properties. Consequently, the maximum absolute values of both tensile and compressive pipeline strains are correlated with the seismic intensity level (i.e., in terms of bedrock offset which is associated with earthquake magnitude via simple relationships). The paper concludes with a set of design charts and tables for the preliminary seismic design of onshore high - pressure gas pipelines. These charts and tables predict with reasonable accuracy pipeline deformations, in terms of strains, for different magnitude, fault type, dip angle, sand type, and varying overlying soil layer thickness.

Experimental qualification of seismic strengthening of URM buildings in Nepal - Hammed O. Aminulai; Marco Baiguera; Duncan A. Crump; Anastasios Sextos; Mohammad M. Kashani (Soil Dynamics and Earthquake Engineering, 2023)

Physical and numerical investigation of integral bridge abutment stiffness due to seasonal thermal loading - Sha Luo; Ziyan Huang; Yazan Asia; Flavia De Luca; Raffaele De Risi; John Harkness; Louis Le Pen; Geoff Watson; David Milne; David Chapman; Anastasios Sextos; Nicole Metje; et al. (Transportation Geotechnics, 2023)

Shaking table test and numerical analyses of a full scale three-leaf masonry wall - Francesco Di Michele; Enrico Spacone; Guido Camata; Giuseppe Brando; Anastasios Sextos; Adam Crewe; George Mylonakis; Matt Diez; Luiza Dihoru; Humberto Varum (Bulletin of Earthquake Engineering, 2023)
This paper discusses the main results of a full-scale shaking table test campaign carried out under the auspices of the EU funded research project SERA, whose objective is to investigate the seismic performance of three-leaf masonry walls with weak lime-mortar joints. These masonry walls are widely found in seismic prone regions in the Mediterranean area, thus assessing their behaviour under dynamic actions is an important pre-requisite for the seismic vulnerability evaluation of a plethora of historical centres. The first part of the paper presents a preliminary study on the mechanical properties of the wall component materials that was carried out through an ad-hoc experimental campaign. The outcomes are of particular interest for the characterization of the mortar and of the infill materials, that were designed to reproduce the low strength that is typically found in old masonry buildings. The design of the masonry wall that was tested and the test set-up are presented next. The applied loading protocol consisted of the horizontal component of a ground motion record that is repeatedly applied to the shaking table with increasing intensity. Finally, the main results of the experimental test are discussed. The damage patterns, drift ratios and base shear are presented for the ground motion sequence. The results are also discussed through a dynamic capacity curve that shows the attainment of different limit states with increasing ground motion intensity. A set of nonlinear numerical simulations, both static and dynamic, using a 3D FE model of the wall verify the experimental study as they report good agreement with the experimental tests and exhibit stable numerical behaviour.

Seismic performance and SSI effects of a two-storey RC school building during the 2014 Cephalonia, Greece, earthquake sequence - Christos Giarlelis; Constantinos Repapis; Evlalia Lamprinou; George Mylonakis; George Manolis; Anastasios Sextos (Bulletin of Earthquake Engineering, 2023)
The response of a two-storey RC school building in the town of Argostoli, Cephalonia Island, Greece, during the seismic sequence of January and February 2014, is examined. The structure was built following an older generation of seismic codes dating from the 1950s, which provide limited strength and ductility against lateral loads. Despite the severity of ground shaking and the two successive events, the building suffered relatively minor damage, like most of the RC buildings in the town. Following a short presentation of some basic seismological, structural and geotechnical aspects of the seismic sequence, the paper focuses on the seismic performance of the structure at hand. To this end, a series of detailed non-linear static and time-history dynamic analyses are reported, which highlight the interplay of soil, foundation and superstructure in modifying the seismic demand. It is demonstrated that SSI had an unexpectedly important (detrimental) role in the behaviour of the structure, increasing its natural period by about 25% and aggravating ductility demand in almost all columns, despite the moderately soft soil conditions (average V S = 180 m/s). The results shed light on the seismic performance of the building and help drawing conclusions on the engineering effects of the 2014 Cephalonia earthquake sequence.

Preface for the Special Issue οn the Μ7.0 Samos Island (Aegean Sea) earthquake of 30th October 2020: reconnaissance missions and first observations - Anastasios Sextos; Kemal Onder Cetin; George Mylonakis; Jonathan Ρ. Stewart (Bulletin of Earthquake Engineering, 2022)

Reconnaissance of 2020 M 7.0 Samos Island (Aegean Sea) earthquake - K. Onder Cetin; George Mylonakis; Anastasios Sextos; Jonathan P. Stewart (Bulletin of Earthquake Engineering, 2022)

Correction to: Liquefaction potential for the Kathmandu Valley, Nepal: a sensitivity study - Rama M. Pokhrel; Charlotte E. L. Gilder; Paul J. Vardanega; Flavia De Luca; Raffaele De Risi; Maximilian J. Werner; Anastasios Sextos (Bulletin of Earthquake Engineering, 2022)

Liquefaction potential for the Kathmandu Valley, Nepal: a sensitivity study - Rama M. Pokhrel; Charlotte E. L. Gilder; Paul J. Vardanega; Flavia De Luca; Raffaele De Risi; Maximilian J. Werner; Anastasios Sextos (Bulletin of Earthquake Engineering, 2022)
An assessment of liquefaction potential for the Kathmandu Valley considering seasonal variability of the groundwater table has been conducted. To gain deeper understanding seven historical liquefaction records located adjacent to borehole datapoints (published in SAFER/GEO-591) were used to compare two methods for the estimation of liquefaction potential. Standard Penetration Test (SPT) blowcount data from 75 boreholes inform the new liquefaction potential maps. Various scenarios were modelled, i.e., seasonal variation of the groundwater table and peak ground acceleration. Ordinary kriging, implemented in ArcGIS, was used to prepare maps at urban scale. Liquefaction potential calculations using the methodology from (Sonmez, Environ Geol 44:862–871, 2003) provided a good match to the historical liquefaction records in the region. Seasonal variation of the groundwater table is shown to have a significant effect on the spatial distribution of calculated liquefaction potential across the valley. The less than anticipated liquefaction manifestations due to the Gorkha earthquake are possibly due to the seasonal water table level.

Empirical seismic fragility models for Nepalese school buildings - Nicola Giordano; Flavia De Luca; Anastasios Sextos; Fernando Ramirez Cortes; Carina Fonseca Ferreira; Jingzhe Wu (Natural Hazards, 2021)
Empirical vulnerability models are fundamental tools to assess the impact of future earthquakes on urban settlements and communities. Generally, they consist of sets of fragility curves that are derived from georeferenced post-earthquake damage data. Following the 2015 Nepal earthquake sequence, the World Bank, through the Global Program for Safer Schools, conducted a Structural Integrity and Damage Assessment (SIDA) of about 18,000 school buildings in the earthquake-affected area. In this work, the database is utilized to identify the main structural characteristics of the Nepalese school building stock. For the first time, extended SIDA school damage data is processed to derive fragility curves for the main structural typologies. Data sets for each structural typology are used for a Bayesian updating of existing fragilities to obtain regional models for Nepalese schools. These fragility estimates can be adopted to assess potential seismic losses of the school infrastructure in Nepal. Additionally, they can be used for calibrating loss assessment studies in the wider Himalayan region where the structural typologies are similar.

Analytical fragility curves for masonry school building portfolios in Nepal - Nicola Giordano; Flavia De Luca; Anastasios Sextos (Bulletin of Earthquake Engineering, 2021)
Schools represent a reference point for communities in any part of the world. Therefore, their safety and resilience against natural catastrophes is of paramount importance. The recent 2015 Gorkha earthquake has unfortunately shown that Nepalese school buildings are highly vulnerable to seismic actions. Most of them are indeed constituted by low-quality unreinforced masonry (URM). The quantification of URM vulnerability is fundamental to estimate the risk associated to school building portfolios at territorial scale. This work discusses statistics available for Nepalese schools and then presents analytical fragility curves for three recurrent URM typologies covering more than 50% of the school building stock. The methodology adopted to derive fragilities is spectral-based and accounts for out-of-plane and in-plane damage potential in a single easy-to-use analytical framework. Inter-building, intra-building and record-to-record variabilities are directly considered in the analysis. The obtained fragilities integrate the studies available for the region and can be used for pre-/post-earthquake risk assessment and prioritization of interventions at country level.

Seismic fragility of buried steel natural gas pipelines due to axial compression at geotechnical discontinuities - Grigorios Tsinidis; Luigi Di Sarno; Anastasios Sextos; Peter Furtner (Bulletin of Earthquake Engineering, 2020)

Influence of structure–foundation–soil interaction on ground motions recorded within buildings - Dimitris Sotiriadis; Nikolaos Klimis; Basil Margaris; Anastasios Sextos (Bulletin of Earthquake Engineering, 2019)

Integrated seismic risk and resilience assessment of roadway networks in earthquake prone areas - Ioannis Kilanitis; Anastasios Sextos (Bulletin of Earthquake Engineering, 2019)

Efficiency of alternative intensity measures for the seismic assessment of monolithic free-standing columns - Athanasios Pappas; Anastasios Sextos; Francesca da Porto; Claudio Modena (Bulletin of Earthquake Engineering, 2017)

A knowledge-based software for the preliminary design of seismically isolated bridges - George C. Manos; Stergios A. Mitoulis; Anastasios G. Sextos (Bulletin of Earthquake Engineering, 2012)

Evaluation of seismic response of bridges under asynchronous excitation and comparisons with Eurocode 8-2 provisions - Anastasios G. Sextos; Andreas J. Kappos (Bulletin of Earthquake Engineering, 2009)